Going after the Addiction, Not the Addicted: The Impact of Drug Decriminalization in Portugal - Sónia Félix; Pedro Portugal; Ana Tavares (Institute of Labor Economics (IZA), 2017)
This paper investigates the impact of drug decriminalization in Portugal using the Synthetic Control Method. The applied econometric methodology compares Portuguese drug-related variables with the ones extracted from a convex combination of similar European countries. The results suggest that a policy change implemented in Portugal contributed to a decrease in the number of heroine and cocaine seizures, a decrease in the number of offenses and drug-related deaths, and a decrease in the number of clients entering treatment. Moreover, the policy change contributed to a reduction in the incidence of drug addicts among HIV individuals.
Keywords: C21; D04; K42; 330; drug decriminalization policy; illicit drugs; synthetic control method